A INFLUÊNCIA DA COBERTURA DO “JORNAL NACIONAL” NA FORMAÇÃO DO DISCURSO DE ÓDIO CONTRA LULA - Pignaton, Caroline de Marchi (2021)
This study puts into perspective the connections between the role of contemporary journalism and hate speech. Through the analysis of French discourse, from the perspective of the pathemic effects of Charaudeau (2007), it analyzes how Jornal Nacional (A Brazilian TV news program) contributes to the formation of hate speech against former president Luiz Inácio Lula da Silva. In this way, it intends to achieve the pathemic discursive strategies produced by this TV news program with the highest audience on Brazilian television in the journalistic coverage of the “Triplex in Guarujá” case, which culminated in Lula's arrest during the 24th phase of “Operação Lava Jato” (Car War Operation). For this, its corpus was outlined based on the procedural stages conveyed by the aforementioned newscast and it comprises editions between the period of January 27, 2016 to June 23, 2021. Initially, it conceptualizes characteristics of the procedural nature of journalism and its relationship with the truth. It also works theoretically to understand the pre-existing relationships that are materialized through speech, whether verbal or non-verbal. Then, it elucidates concepts that permeate what Muniz Sodré (2016) calls sensitive discourse strategies, used by political journalism as a form of power and audience attraction. It verifies how telejournalism discourse explores emotions seeking to generate an enunciative behavior among viewers through the movement of affections and how this strategy is inserted in the formation of hate speech.